2022
DOI: 10.1186/s40795-022-00612-w
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 epidemic lockdown-induced remarkable decrease in dairy products consumption of Iran population: does it really matter? National Food and Nutrition Surveillance

Abstract: Background The pandemic of the newly emerged coronavirus infection and its related disease, Covid-19, has influenced various aspects of human life including dietary habits. This study aimed to examine changes in dairy products consumption during Covid-19 lockdown period in a huge sample of Iranian households. Methods A cross-sectional descriptive-analytical study using a web-based electronic self-administered questionnaire designed to detect any ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Interestingly, our study also revealed that female-headed households tend to consume more cheese and total dairy while have lower milk consumption. This finding is in contrast with other studies that have shown female-headed households have lower dairy consumption ( 58 , 77 ) probably due to their limited resources. However, our study also found a positive relationship between female-headed households and cheese consumption.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Interestingly, our study also revealed that female-headed households tend to consume more cheese and total dairy while have lower milk consumption. This finding is in contrast with other studies that have shown female-headed households have lower dairy consumption ( 58 , 77 ) probably due to their limited resources. However, our study also found a positive relationship between female-headed households and cheese consumption.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings show that although cheese consumption (mainly white cheese) has a slower decreasing trend, its overall trend indicates an increase. Most Iranians consume cheese with bread for breakfast, making cheese consumption a part of their food culture ( 58 ). This could justify the slower decreasing trend, and the study’s findings align with those of other studies ( 58 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations